2008
DOI: 10.1111/j.1439-0523.2008.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Rht‐D1 dwarfing locus on Fusarium head blight rating in three segregating populations of winter wheat

Abstract: Fusarium head blight (FHB) is one of the major fungal diseases in wheat throughout the world. To control FHB severity, breeding genetically resistant varieties is thought to be the most promising strategy. In wheat breeding programmes, short cultivars predominantly carrying the Norin 10 derived semi-dwarfing allele Rht-D1b (Rht2) are preferred worldwide because of higher achievable grain yields and lower risk of lodging. This study was conducted to determine the influence of different alleles at the Rht-D1 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 34 publications
(58 reference statements)
5
33
1
Order By: Relevance
“…Selecting taller GA insensitive genotypes is an approach that was found advantageous for the examined Central European conditions (Šíp et al 1988), and it can be feasible also for the high yielding environments of Northwest Europe (Mathews et al 2006), where not using the rht-D1b allele would lead to a considerable yield penalty. The obtained results indicate that it is possible to achieve improved FHB resistance also in genotypes carrying rht-D1b, however, in accordance with the findings of Voss et al (2008) Table 5. Results of testing the differences between mean VSS (visual symptom score on 1-9 scale; 1 = low incidence) of GA insensitive (rht-D1b) and GA sensitive lines in relation to different plant height categories it becomes increasingly difficult (but not impossible) with large height reductions.…”
Section: Analysis Of Relations Between the Variety Response To Fhb Ansupporting
confidence: 81%
See 2 more Smart Citations
“…Selecting taller GA insensitive genotypes is an approach that was found advantageous for the examined Central European conditions (Šíp et al 1988), and it can be feasible also for the high yielding environments of Northwest Europe (Mathews et al 2006), where not using the rht-D1b allele would lead to a considerable yield penalty. The obtained results indicate that it is possible to achieve improved FHB resistance also in genotypes carrying rht-D1b, however, in accordance with the findings of Voss et al (2008) Table 5. Results of testing the differences between mean VSS (visual symptom score on 1-9 scale; 1 = low incidence) of GA insensitive (rht-D1b) and GA sensitive lines in relation to different plant height categories it becomes increasingly difficult (but not impossible) with large height reductions.…”
Section: Analysis Of Relations Between the Variety Response To Fhb Ansupporting
confidence: 81%
“…The effect of rht-B1b on FHB resistance could not be evaluated in this variety set, because only one variety (a moderately resistant variety Baletka) was found to carry this gene. The association of FHB susceptibility with the dwarfing allele rht-D1b was recently documented in many publications (Draeger et al 2007;Holzapfel et al 2008;Srinivasary et al 2008;Voss et al 2008) and this association is also supported by the finding that e.g. UK winter wheat varieties, the great majority of which carry the rht-D1b allele, are generally highly susceptible to FHB (Draeger et al 2007;Gosman et al 2007).…”
Section: Analysis Of Relations Between the Variety Response To Fhb Anmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, Holzapfel et al (2008) showed on three sets of RILs between European winter wheats that the rht-D1 genomic region is the major source of variation in FHB resistance in the European wheat gene pool. Analogously to Voss et al (2008), they also obtained semi-dwarf lines with acceptable levels of FHB resistance due to the effects of other minor QTLs. rht-B1b allele at rht-B1 locus seems to have a less negative effect, especially on Type II resistance (Srinivasachary et al 2009).…”
Section: Types and Mechanisms Of Fhb Resistancementioning
confidence: 98%
“…Similar results were obtained by Buerstmayr et al (2008) from the evaluation of FHB resistance in recombinant lines derived from the crosses Arina/Forno, Arina/Riband, Dream/Lynx, G16-92/Hussar, Renan/Récital, SVP-72017/Capo and Capo/Sumai 3 under natural conditions at different locations in Europe. However, Voss et al (2008) showed on a set of three segregating populations of winter wheat that the correlation between the presence of rht-D1b allele and FHB resistance is not absolute, i.e. lines carrying rht-1Db allele with a relatively high level of FHB resistance can be obtained.…”
Section: Types and Mechanisms Of Fhb Resistancementioning
confidence: 99%